Pengaruh Likuiditas, Ukuran Perusahaan, Dan Sales Growth Terhadap Struktur Modal Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di BEI Tahun 2019-2021 - Alfida Salfa Anisa; Akhmad Naruli; Agus Athori (International Forum of Researchers and Lecturers, 2023)
The purpose of this research is to dissect the relationship between capital structure and variables including liquidity, business size, and sales growth. A crude measure of liquidity, the current ratio formula may be found here. A company's size is sometimes described in terms of its Ln (total assets). The debt-equity ratio is used to assess the firm's financial health, and sales growth is calculated by contrasting t+1 with t sales. Researchers employ purposeful sampling to pick research participants from a broader community so that their findings are generally applicable and applicable to the study's goals. Purposive sampling allowed us to gather information from 69 separate companies trading on the Indonesia Stock Exchange within the property and real estate industry for the years 2019 and 2020. The research concluded that liquidity had a positive effect on capital structure